EPIDEMIOLOGICAL PROFILE OF POISONING CASES AUTOPSIED AT AUTOPSY CENTRE, RIMS, RANCHI (Journal of Forensic Medicine & Toxicology, 2025)
Background: The National Crime Record Bureau reports poisoning as one of the most prevalent causes of increased rates of suicide and accidental mortalities. There are different agents, such as insecticides and drugs have been used for accidental and intentional poisoning substances. The convenient accessibility of organophosphates and aluminum phosphide, along with the non-availability of specific antidotes. Therefore, this study was conducted to know the current scenario of poisoning deaths in the Jharkhand state. Materials & Methods: This retrospective study was carried out on 120 cases of death due to poisoning in the Department of Forensic Medicine & Toxicology of Rajendra Institute of Medical Sciences, Ranchi between 20th June 2022 to 20th June 2023. Information regarding the socio-demographics, time of incidence, place of incidence, occupation, etc., were collected from the various medico-legal documents and Comprehensive interviews were carried out with the family members and police officials present with the deceased individuals. Results: The proportion of males (64.1%) was higher than the females (35.8%). The poisoning incidence was reported to be the highest in the 16 to 30 years group. Mental instability contributed causes (41.6%) of the total deaths. The maximum mortalities occurred in late night hours (between 12 AM and 4 AM). Females exhibited a greater inclination towards morning hours, whereas males showed a preference for the evening and night time. Organophosphates (54.1%) were the most prevalent poisoning substance, afterward Aluminum phosphide (20 %), Phenyl (4.5%), Alcohol (4.6%), All-out liquid vaporizer (1.2%), and Datura seeds (1.2%). Conclusion: The current study's findings are largely consistent with those from earlier studies conducted in India. In this study, organophosphate came up as the most common poisoning agent, causing the highest mortality in poisoning cases.
Keywords: Poisoning; socio-demographics; poisoning agents; Jharkhand